THE ANALYSIS ON THE EFFECTS OF DEPOSIT INTEREST RATE, MONEY SUPPLY AND INFLATION ON HOUSEHOLD CONSUMPTION IN INDONESIA DURING 1983-2013 - Fachrudin, Feri; Wahyudi, Setyo Tri (Jurnal Ilmiah Mahasiswa FEB, 2014)
The aim of  this  research  is  to  acknowledge the macroeconomic variable’s influences of  interest rate deposit, the amount of money supply (M2), and the inflation to the household’s consumption in Indonesia. The data used in this research is time series data from 1983 to 2013. After studying literature and testing the data using Error Correction Model (ECM) method, it showed that Interest Rate Deposit, money supply (M2) and inflation simultaneously have a significant effect in short term period and longed term period. Partially, Interest Rate Deposit has an unsignificant negative effect, The sum of money supply (M2) has a significant positive effect, and the inflation has a significant negative effect  to  the household’s consumption in short term period. While in longed term period, Interest Rate Deposit has a significant negative effect, the sum of money circulation (M2) and the inflation have a significant positive effect to the household’s consumption. Keywords:  Household Consumption, Deposit Interest Rate, Money Supply (M2), Inflation, Error Correction Model (ECM).